2015
DOI: 10.1148/radiol.14141715
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Spastic Paraplegia: Beyond Clinical Phenotypes toward a Unified Pattern of Central Nervous System Damage

Abstract: The detection of a distributed pattern of central nervous system damage in patients with pure and complicated HSP suggests that the "primary" corticospinal tract involvement known to occur in these patients may be associated with a neurodegenerative process, which spreads out to extramotor regions, likely via anatomic connections. This observation is in line with emerging pieces of evidence that, independent of the clinical phenotype, there is a common neurodegenerative cascade shared by different neurologic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 39 publications
5
34
0
2
Order By: Relevance
“…However, given the small size of our sample, such conclusion needs to be confirmed. Nevertheless, this reflects the rarity of these conditions, and it is in line with previous neuroimaging studies in these patients [ 17 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, given the small size of our sample, such conclusion needs to be confirmed. Nevertheless, this reflects the rarity of these conditions, and it is in line with previous neuroimaging studies in these patients [ 17 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 89%
“…We found no correlation between the severity or duration of the disease and the degree of spinal cord atrophy, as reported by others in distinct subtypes of hereditary spastic paraplegias (Hedera et al, 2005;Agosta et al, 2015). Moreover, as in an earlier study of patients with adrenomyeloneuropathy (Dubey et al, 2005), we found no correlation between disease severity and DTI-derived measures along the corticospinal tract in the brain.…”
Section: Discussionsupporting
confidence: 76%
“…Quantitative MRI has been largely used for identifying, characterizing and quantifying structural changes of the brain in many neurological diseases, including hereditary neurodegenerative diseases and hereditary spastic paraplegias (Mascalchi et al, 2004;Rosas et al, 2006;Agosta et al, 2015). Moreover, quantitative MRI-derived measures of the brain might reveal longitudinal changes that make them attractive as surrogate outcome measures (Harrison et al, 2011;Poudel et al, 2015), despite their external validity is still a matter of concern (Rothwell, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The common DTI indices are: fractional anisotropy, a measure of sensitivity to changes in orientation of axons along the tracts; mean diffusivity, a measure of magnitude of water diffusion and the presence of obstacles to diffusion [14,15], and radial diffusion, used to differentiate axonal injury from demyelination [13]. The most common radiological changes in a variety of HSP gene mutations are alterations in the corticospinal tract (70% of all studies, 71% of SPAST studies) and corpus callosum (80% of all studies, 86% of SPAST studies) [16,17,18,19,20,21,22,23,24,25]. Loss or damage to axons in the corticospinal tract are consistent with the motor symptoms of the disease, although white matter disturbances are not confined to the corticospinal tract and corpus callosum with involvement at the whole brain level, frontal and temporal lobes, cerebellum, and other regions.…”
Section: Radiology Of Hspmentioning
confidence: 99%
“…These changes are consistent with widely distributed axonal damage in the white matter of the brain, including the corticospinal tract, which contains the axons of the motor neurons projecting to the lower motor neurons in the distal spinal cord, whose degeneration is responsible for the clinical manifestations of HSP. There is evidence for correlation between radiological findings and disease severity and duration [16,17,19,24]. Future clinical investigations could consider examining late-stage SPAST HSP patients for evidence of non-motor manifestations that are seen in patients with other HSP mutations [27].…”
Section: Radiology Of Hspmentioning
confidence: 99%